Arthroscopic Bankart repair versus conservative treatment after primary anterior glenohumeral dislocation in patients under 25 years of age: A prospective randomized study. Issue 2 (28th February 2020) - Hardy, Alexandre; Pougès, Cécile; Duriez, Pauline; Vervoort, Thomas; Lalanne, Clément; Bourgault, Caroline; Demondion, Xavier; Szymanski, Christophe; Chantelot, Christophe; Maynou, Carlos
Background: Conservative treatment after primary anterior shoulder dislocation (ASD) is associated with a high recurrence rate in young patients. The main objective was to compare primary arthroscopic Bankart repair and conservative treatment 2 years after primary ASD in patients less than 25 years old. Methods: A prospective randomized study was conducted in patients between 18 to 25 years old after primary ASD. The first group had arthroscopic Bankart repair within 15 days and the second group was treated conservatively. Patients in both groups were immobilized in internal rotation for 3 weeks and followed the same rehabilitation protocol. Patients were clinically monitored in 3, 6, 12 and 24 months. The main outcome criterion was recurrent dislocation, subluxation or apprehension when the arm was placed in 90° abduction and external rotation. Secondary outcome criteria were functional scores (Quick-DASH, Walch-Duplay, WOSI), joint mobility and resumption of sports. Results: 40 patients were included (20 in the surgical group and 20 conservative group). The average age was 21 +/- 1.8 years with 33 men (82.5%) and 7 women (17.5%). Patients in the surgical group underwent surgery within an average of 4.3 +/- 2.4 days. In the surgical group, instability at 2 years was significantly less than in the conservative group (2 (10%) compared to 14 (70%); p=0.0001). Fewer patients had a recurrence (0 versus 6 (30%)), subluxation (2 (10%) versus 13 (65%); p=0.003), and apprehension (1 (5%) versus 11 (58%); p=0.0005). The Quick-DASH (6.5 versus 11.2 points), Walch-Duplay (88.4 versus 70.3 points; p=0.007) and WOSI (11.5 versus 17.7 points; p=0.035) functional scores were better in the surgical group at 2 years. 95% had resumed sport in the surgical group compared to 68% in conservative group. No per- or postoperative complications were reported. There was no significant difference in joint mobility. Conclusion: After primary ASD in young patients, arthroscopic Bankart repair decreased recurrent instability at 2 years and provided better functional recovery than conservative treatment.